Citizens' intertemporal perspectives on municipal mergers and the role of deliberation for these - Strandberg Kim; Leino Mikko; Lindell Marina; Christensen Henrik Serup; Setälä Maija (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This article studies citizens' intertemporal opinions in the context of a proposed municipal merger in Finland in 2019. We ask how important citizens regard short- and long-term aspects of politics concerning the merger. Using a survey sent to a random sample of citizens (N = 320), we studied the impact of a Citizens' Jury on developing intertemporal opinions. This was done partially by tracing the development of intertemporal opinions of the jurors (N = 21) and partially through a survey experiment among the population in the municipality. The survey experiment (N = 174) analyzed the effect of reading a written statement by the Citizens' Jury on various opinions, including intertemporal opinions. The findings show that, in the initial survey, citizens valued long-term consequences more than short-term ones in the context of the merger. Similar findings were discovered among the Citizens' Jury, and reading the Citizens' Jury's statement did not produce any statistically significant differences in intertemporal opinions. However, our findings reveal that citizens' vote intentions in a forthcoming referendum on the merger are strongly associated with whether they focused on long-term costs or long-term benefits.